The effect of tax avoidance and corporate governance on the annual report's readability - Ihsanu Ramdan Mustofa; Azas Mabrur (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2022)
This study examines the effect of tax avoidance and corporate governance on the readability of annual reports. The readability of the annual report is measured using a gunning fog index. This quantitative research uses panel data regression analysis with a random effects model. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2016-2019. The sample was selected using the purposive sampling method so that the selected sample in this study amounted to 196 observations. The results provide empirical evidence that tax avoidance affects the readability of the annual report negatively, while managerial ownership positively affects the readability of the annual report. Meanwhile, independent commissioners and audit committees have no significant influence. The results of this study can assist investors in determining which investment decisions they will choose and help tax authorities to allocate more resources to understand public financial statements, especially those that are not easy to read.AbstrakPenelitian ini bertujuan untuk menguji pengaruh tax avoidance dan corporate governance terhadap keterbacaan laporan tahunan. Keterbacaan laporan tahunan diukur menggunakan proxy berupa gunning fog index. Penelitian ini merupakan peneitian kuantitatif menggunakan analisis regresi data panel dengan model random effect. Populasi penelitian ini adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) selama kurun waktu 2016-2019. Sampel dipilih menggunakan metode purposive sampling sehingga terpilih sampel dalam penelitian ini berjumlah 196 observasi. Hasil pengujian memberikan bukti secara empiris bahwa Tax avoidance berpengaruh negatif terhadap keterbacaan laporan tahunan, sedangkan Kepemilikan manajerial berpengaruh positif terhadap keterbacaan laporan tahunan. Sementara itu komisaris independen dan komite audit tidak bepengaruh signifikan keterbacaan laporan tahunan. Hasil penelitian ini dapat membantu investor dalam menentukan keputusan investasi mana yang akan mereka pilih serta membantu otoritas pajak untuk mengalokasikan lebih banyak sumber daya untuk memahami laporan keuangan publik, terutama yang tidak mudah dibaca.